Evaluation and comparison of different analytical models and design codes in predicting the punching shear strength of reinforced concrete flat slabs without shear reinforcement - Piyush, Kumar Sharma (2014)
Reinforced concrete flat slab system has become an economical structural solution for most buildings because of its ease of construction (no difficulty in placement of formworks), less construction time, lower storey height and maximum freedom in architectural design